A Review of the Clinical Presentation, Causes, and Diagnostic Evaluation of Increased Intracranial Pressure in the Emergency Department - Cristiana Olaru; Sam Langberg; Nicole Streiff McCoin (Western Journal of Emergency Medicine)
Increased intracranial pressure (ICP) is encountered in numerous traumatic and non-traumatic medical situations, and it requires immediate recognition and attention. Clinically, ICP typically presents with a headache that is most severe in the morning, aggravated by Valsalva-like maneuvers, and associated with nausea or vomiting. Papilledema is a well-recognized sign of increased ICP; however, emergency physicians often find it difficult to visualize the optic disc using ophthalmoscopy or to accurately interpret digital fundus photographs when using a non-mydriatic retinal camera. Emergency ultrasound can evaluate the optic nerve sheath diameter (ONSD) and optic disc elevation to determine whether increased ICP is present, however, the studies have been small with different definitions and measurements of the ONSD. The ONSD threshold values for increased ICP have been reported anywhere from 4.8 to 6.3 millimeters. Neuroimaging is the next step in the evaluation of patients with papilledema or high clinical suspicion of increased ICP, as it can identify most structural causes or typical radiological patterns of increased ICP. Neuroradiographic signs of increased ICP can be helpful in suggesting idiopathic intracranial hypertension (IIH), especially when papilledema is absent. Patients with papilledema and normal neuroimaging may undergo lumbar puncture as part of their clinical workup. The cerebrospinal fluid (CSF) opening pressure remains one of the most important investigations to establish the diagnosis of IIH. A CSF evaluation is also required to exclude other etiologies of elevated ICP such as infectious, inflammatory, and neoplastic meningitis. Invasive ICP measurement remains the standard to measure and monitor this condition.